Leveraging cyber resilience using cloud services - Noronha, L. M.; Coutinho, C. (Procedia Computer Science, 2025)
Public cloud services consist of infrastructure, platforms or software hosted by third-parties which are made available over the Internet to end users. Organizations have adopted cloud services when selecting new applications or migrating application workloads to cloud providers, mainly because of their flexibility, scalability, and low entry cost. Security has been a topic of debate because of privacy concerns and the public cloud's inherent exposure to the Internet. The current work intends to assess how cloud services can be a strategic tool in improving an organization's cybersecurity posture. Not only some attack vectors can be reduced but cyber resilience can be setup faster using readily available cloud services. In this article we perform a systematic literature review on these topics, and design a decision support system to help application architects select cloud services from different Cloud Service Providers and make the best use of them to improve an organization's security posture and cyber resilience.